Associations Between Maternal Post-traumatic Stress Disorder and Traumatic Events With Child Psychopathology: Results From a Prospective Longitudinal Study - Glaus, Jennifer; Pointet Perizzolo, Virginie; Moser, Dominik A.; Vital, Marylène; Rusconi Serpa, Sandra; Urben, Sébastien; Plessen, Kerstin J.; Schechter, Daniel S. (Frontiers in Psychiatry, 2021)
Introduction: Exposure to interpersonal violence (IPV) can lead to post-traumatic stress disorder (PTSD) in mothers, and in turn adversely affect the mother-child relationship during early development, as well as the mental health of their children. Our objectives are to assess: (1) the association of maternal IPV-PTSD to child psychopathology, (2) the association of maternal IPV independently of PTSD to child psychopathology, and (3) the relationship between child exposure to violence to the psychopathology of these children. Methods: We used data from the longitudinal Geneva Early Childhood Stress Project. The sample included 64 children (mean age at Phase 1 = 2.4 [1.0-3.7] years) of mothers with or without IPV-PTSD. Data on mothers was collected during Phase 1, using the Clinical Administered PTSD Scale (CAPS), the Brief Physical and Sexual Abuse Questionnaire (BPSAQ) and the Conflict Tactics Scale (CTS2). Modules of a semi-structured diagnostic interview, and the Violence Exposure Scale were used to collect information on child at Phase 2, when children were older (mean age = 7.02 [4.7-10]). Results: A higher CAPS score in mothers when children were toddler-age was associated with an increased risk of symptoms of attention deficit/hyperactivity disorder (ADHD; β=0.33, p=0.014) and PTSD in school-age children. The association between maternal IPV-PTSD and child PTSD (β=0.48, p<.001) symptoms remained significant after adjustment for potential confounders. Among children, exposure to violence was associated with an increased risk of symptoms of generalized anxiety (β=0.37, p=0.006), major depressive (β=0.24, p=0.039), ADHD (β=0.27, p=0.040), PTSD (β=0.52, p<0.001), conduct (β=0.58, p=0.003) and oppositional defiant (β=0.34, p=0.032) disorders. Conclusion: Our longitudinal findings suggest that maternal IPV-PTSD during the period of child development exert an influence on the development of psychopathology in school-aged children. Mothers’ IPV was associated with child psychopathology, independently of PTSD. Child lifetime exposure to violence had an additional impact on the development of psychopathology. Careful evaluation of maternal life-events is essential during early childhood to reduce the risk for the development of child psychopathology. Early efforts to curb exposure to violence in children and early intervention are both needed to reduce further risk for intergenerational transmission of trauma, violence, and related psychopathology.